Effects of posture on carbon dioxide responsiveness in patients with obstructive sleep apnoea. Issue 5 (May 1993) - Satoh, M; Hida, W; Chonan, T; Okabe, S; Miki, H; Taguchi, O; Kikuchi, Y; Takishima, T
Abstract : BACKGROUND–It is well known that upper airway resistance increases with postural change from a sitting to supine position in patients with obstructive sleep apnoea (OSA). It is not known, however, how the postural change affects the ventilatory and occlusion pressure response to hypercapnia in patients with OSA when awake. METHODS–The responses of minute ventilation (VE) and mouth pressure 0.1 seconds after the onset of occluded inspiration (P0.1) to progressive hypercapnia (delta VE/delta PCO2, delta P0.1/delta PCO2) both in sitting and supine positions were measured in 20 patients with OSA. The ratio of the two (delta VE/delta P0.1) was obtained as an index of breathing efficiency. The postural changes in response to carbon dioxide (CO2) after uvulopalatopharyngoplasty (UPPP) were also compared in seven patients with OSA. RESULTS–There were no significant changes in the resting values of end tidal PCO2, P0.1, or VE between the two positions. During CO2 rebreathing, delta VE/delta PCO2 did not differ between the two positions, but delta P0.1/delta PCO2 was significantly higher in the supine than in the sitting position (supine, mean 0.67 (SE 0.09) cm H2O/mm Hg; sitting, mean 0.57 (SE 0.08) cm H2O/mm Hg), and delta VE/delta P0.1 decreased significantly from the sitting to the supine position (sitting, 4.6 (0.4) l/min/cm H2O; supine, 3.9 (0.4) l/min/cm H2O). In seven patients with OSA who underwent UPPP, delta VE/delta P0.1 improved significantly in the supine position and postural change in delta VE/delta P0.1 was eliminated. CONCLUSIONS–These results suggest that in patients with OSA the inspiratory drive in the supine position increases to maintain the same level of ventilation as in the sitting position, and that the postural change from sitting to supine reduces breathing efficiency. Load compensation mechanisms of patients with OSA appear to be intact while awake in response to the rise in upper airway resistance.